How to win the Bachelor : the secret to finding love and fame on America's favorite reality show - Kultgen, Chad, 1976-; Pace, Lizzy (Gallery Books, 2022)
"Since its premiere in 2002, ABC's The Bachelor has become a staple of American television. Now, discover the fascinating history of the show, uncover the ins and outs of the phenomenon that has become Bachelor Nation, and take a deeper look at what separates the winners from the losers. From how best to exit the limo on Night One, to strategies for making a run for the all-important First Impression Rose, to how to avoid being labeled a villain, this clear-eyed guide illustrates the rules and strategies any would-be contestant should know. The ultimate must-read for every fan, How to Win the Bachelor gives you an inside look at the franchise where The Rose holds all the power."Amazon.com